OVERVIEW OF ANTIBIOTIC USE USING ATC/DDD METHOD IN KUALA LEMPUING HEALTH CENTER, BENGKULU CITY, 2020-2021 - Mitha Selpana; Zamharira Muslim; Avrilya Iqoranny Susilo (Poltekkes Kemenkes Bengkulu, 2023)
The high use of antibiotics in every region of Indonesia causes a high possibility of irrational use of antibiotics. this study is to find out how the use of antibiotics using the ATC/DDD method is described at the Kuala Lempuing Health Center, Bengkulu City in 2020 and 2021. The type of research is descriptive in nature with a purposive sampling technique using the ATC/DDD method on outpatient prescriptions containing antibiotics. The results of this study showed The most widely used antibiotic is amoxicillin. The total value of DDD/1000 KPRJ at the Kuala Lempuing Health Center the total DDD/1000 KPRJ value during 2020 was 3873.4 and in 2021 it increased to 4591.3. This study concludes Amoxicillin is the most widely used antibiotic. The highest total value of DDD/1000 KPRJ at the Kuala Lempuing Health Center occurred in 2021.